2015
DOI: 10.7717/peerj.748
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of telenutrition in a women’s weight loss program

Abstract: Objective. The objective of this study is to evaluate the effectiveness of telenutrition versus traditional nutritional consultations for female obese patients in need of nutritional treatment.Methods. A comparative clinical study was conducted among 233 obese or overweight women (including 20 who dropped out and 60 who failed) who consulted a nutrition clinic in Barranquilla (Colombia) for nutritional assessment and chose either telenutrition or a traditional consultation that included a weekly follow-up cons… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 20 publications
0
4
0
2
Order By: Relevance
“…A previous study in women with obesity without physical disability showed tele-nutrition using e-mail and computer-based chat had a failure or drop-out rate half that of those in the traditional in-person consultation group and showed a small but statistically significant difference in weight loss. 22 By reducing barriers to treatment through tele-nutrition, a study such as this may result in increased retention and subsequently improved outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study in women with obesity without physical disability showed tele-nutrition using e-mail and computer-based chat had a failure or drop-out rate half that of those in the traditional in-person consultation group and showed a small but statistically significant difference in weight loss. 22 By reducing barriers to treatment through tele-nutrition, a study such as this may result in increased retention and subsequently improved outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Aunque este estudio no ha buscado la relación de la depresión con el estado nutricional y el estado civil independiente de su tratamiento; ha encontrado resultados interesantes en otras variables. Kuzmar, Cortés, Rizo, 2014;Kuzmar et al, 2015) Es importante resaltar que no se encontró una asociación entre el sexo femenino y la presencia de depresión(47% comparado con los varones que fue de 53%) (Chi cuadrado 1,713avp: 0,158) , contrario a lo señalado en diversos estudios (Field et al, 2003), aunque esto pudo deberse a que la población general de estudiantes mujeres solo representan el 32,5%. Otro hallazgo del estudio consistió en que el nivel socioeconómico medio fue el que más prevaleció (con un 93%, Chi cuadrado: 1,232aVp: 0,540), lo que puede explicarse porque el 84.4% de toda la población pertenece a este nivel socioeconómico.…”
Section: Resultsunclassified
“…Kuzmar IE et al, reported similar results, with no significant differences in weight loss, BMI and waist-to-height ratio (WHtR), when comparing the in-person assessment to telenutrition, in obese women. 17 …”
Section: Discussionmentioning
confidence: 99%